Strategy to Increase Community Participation in the Development of Bah Damanik Bathing Nature Tourism in Sidamanik District, Simalungun Regency - Ahmad Rizky Setiawan; Ade Kurnia Harahap; Anggiat sinurat (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Tourism is a sector that is currently being widely discussed, the Tourism Sector is very promising in terms of increasing the economy for the community and government. The development of tourist attractions can provide tourist comfort, making visitors interested in returning to visit. Bah Damanik Bathing Nature Tourism in Sidamanik District, Simalungun Regency is one of the most interesting natural tourist attractions. This study aims to determine the Strategy to Increase Community Participation in the Development of Bah Damanik Bathing Nature Tourism. The method used is a qualitative SWOT analysis approach. This research is in Bah Damanik Bathing Nature Tourism. The population is 50 people, the total population is used as a sample. Data collection by conducting observations, documentation and interviews. The results of the study showed a Strategy to Increase Participation by Building road infrastructure from Village Fund Allocations and repairing public bathrooms from community donations in the form of materials. Professionalism of Bah Damanik Bathing Nature Tourism Management, namely Increasing community income by empowering them as collectors of entrance fees and cleanliness guards. Strategy to develop the potential of Bah Damanik Bathing Nature Tourism. requires the Role of the Regional Government because it has Uniqueness and beauty, natural nature, fresh air, the existence of seven charm elements, community culture that accepts the presence of tourists. To improve the Development of Bah Damanik Bathing Nature Tourism. The government and community leaders build road infrastructure, increase economic activities and implement socio-culture. Bah Damanik Bathing Nature Tourism Management conducts training, innovation and holds events. The development of facilities and infrastructure for Bah Damanik Bathing Nature Tourism continues to be carried out in order to provide comfort for tourists.